Sustainable Freight Transport Theory, Models, and Case Studies (Operations Research/Computer Science Interfaces Series,, 2018)
This book presents the latest technologies and operational methods available to support sustainable freight transport practices. It highlights market requirements, cutting edge applications, and case studies from innovators in the logistics services industry. The goal is to help bridge the gap between advanced computational techniques and complex applied problems such as those in sustainable transport and logistics operations. Freight transport has traditionally focused on costs and service levels. However, it is no longer possible or socially responsible to neglect the environmental, social, climate, and energy implications of the freight moving globally. This book places sustainability at the forefront of the freight transport agenda. Sustainable Freight Transport: Theory, Models and Case Studies is divided into four sections. Section I includes chapters that focus on green freight transport policies and existing frameworks and issues. Section II is devoted to using modelling techniques and optimization for achieving sustainable freight transport, while Section III examines vehicle technologies and information systems that help achieve more sustainable transport operations both locally and globally. The final section focuses on the market requirements and presents case studies from key logistics service providers in achieving sustainable freight transport including intermodal transport applications. The contributions come from authors from different areas, backgrounds, and countries to offer a global perspective.